2011
DOI: 10.1097/ccm.0b013e3181ffde1c
|View full text |Cite
|
Sign up to set email alerts
|

Pleth variability index predicts fluid responsiveness in critically ill patients*

Abstract: The pleth variability index can predict fluid responsiveness noninvasively in intensive care unit patients under mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 44 publications
4
93
2
1
Order By: Relevance
“…Studies have shown the usefulness of this noninvasive dynamic parameter in mechanically ventilated patients in the operating room and in the intensive care unit (ICU). 6,10,19 Conversely, other studies have concluded that PVI was of limited value in predicting fluid responsiveness in laparoscopic surgery 20 and in the ICU setting, respectively. 21 Several observations have shown the limitations of this parameter.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown the usefulness of this noninvasive dynamic parameter in mechanically ventilated patients in the operating room and in the intensive care unit (ICU). 6,10,19 Conversely, other studies have concluded that PVI was of limited value in predicting fluid responsiveness in laparoscopic surgery 20 and in the ICU setting, respectively. 21 Several observations have shown the limitations of this parameter.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, the PVI has been labelled a predictor of fluid responsiveness [5][6][7] however, it is unclear whether this parameter can also be used in patients with nerve blocks. It is possible that the application of local anesthetics might result in changes in the state of peripheral perfusion, which could influence the accuracy of PVI to predict changes in preload reliably following volume expansion.…”
Section: Résumémentioning
confidence: 99%
“…[54][55][56][57][58] Solus-Biguenet et al, for instance, found a weak correlation of 0.29. 54 Nevertheless, despite this weak correlation, the majority of fluid responsiveness studies suggest that the respiratory variation in the PPG tracing is predictive of the hemodynamic response to fluid loading, [59][60][61][62][63] although this finding is not universal. 64,65 Surprisingly, despite the fact that the physiologic meaning of arterial respiratory variation has been understood for decades, extrapolation to the PPG waveform was completely missed by the manufacturers of pulse oximeters who considered this information ''noise'' and filtered it out through the application of high-pass filters.…”
Section: Fluid Responsivenessmentioning
confidence: 86%
“…Several studies have confirmed that PVI can predict the cardiovascular response to both passive leg raising 81 and fluid administration in patients whose lungs are mechanically ventilated. [82][83][84][85] Despite the growing body of data suggesting that PVI is capable of predicting fluid responsiveness, there does not seem to be strong agreement between PVI and PPV. [86][87][88][89][90] The reasons for this paradox (excellent predictor of fluid responsiveness yet not in agreement with arterial-derived metrics) are not clear but may be related to the dependence of PVI on perfusion.…”
Section: Technological Assessmentmentioning
confidence: 99%